A Pragmatics Implicature Function Of Hillary Clinton And Donald Trump Presidential Debate - Ulfani Rizki Nasir (Jurnal Ilmiah Langue and Parole, 2017)
The problem in this thesis is the utterances by the candidate of presidential debate Hillary Clinton and Donald Trump to get the support from the audience and can be a President of America. The candidates give suggestion and negative comment for the audience that he or she was the best to be a president of America. In this writing, The writer use qualitative method of collecting data because of the element that used come from textual material, which data collected with utilize all of the information and the relevant thought. The writer use library research that kinds of qualitative method for analyze the data. Sarwono (2006:226) mention that library research use for analyze from textual data with systematically. In the writer point of view, this method is correctly use for analyzing this proposal. The writer will collect the data and categorized the primary data to secondary data with used pragmatics implicature function that is assertive function, directive function and expressive function and choose only some of the data for sampling. The results of research in this thesis are the function of pragmatics implcature that was used the most is expressive function. From three presidential debate if Hillary Clinton and Donald trump.